Green production of silver nanoparticles from Cassia occidentalis and Alternanthera pungens and evaluation of their nematicidal activity against Meloidogyne javanica - Navaneetha Krishnan Ayyankalai; Palanisamy Sundararaj; Manikantan Gurumoorthy Baskar; Nallusamy Duraisamy; Sakthivel Muthu; Mythileeswari Lakshmikanthan; Gholamreza Abdi (Scientific Reports)
Abstract In this study, silver nanoparticles (AgNPs) were synthesized through an eco-friendly bioreduction process using plant extracts from Cassia occidentalis and Alternanthera pungens. The formation of AgNPs was confirmed by a visible color change in the reaction mixture, followed by characterization using UV-Vis spectroscopy, SEM-EDX, FTIR, XRD, zeta potential, and dynamic light scattering (DLS) analysis. UV-Vis spectroscopy revealed characteristic surface plasmon resonance (SPR) peaks at 420 nm and 425 nm for C. occidentalis and A. pungens, respectively. EDX analysis confirmed a high silver content, while SEM images depicted irregularly distributed nanoparticles with spherical and cylindrical morphologies. FTIR spectra indicated the involvement of various functional groups in nanoparticle stabilization, and XRD analysis verified their crystalline structure. DLS measurements indicated an average nanoparticle size of approximately 100 nm, while zeta potential analysis suggested good colloidal stability. The nematicidal potential of AgNPs was assessed against second-stage juveniles (J2) of Meloidogyne incognita, exhibiting dose-dependent toxicity with an LC₅₀ value of 0.5 mg/L. Field experiments on tomato plants demonstrated a significant reduction in nematode infestation at higher AgNP concentrations, highlighting their potential as an eco-friendly alternative for nematode management in agriculture.